Nurses’ Preparedness regarding Emerging Infectious Diseases (EID) in Selected Hospitals of Maharashtra (India) - Joshi Sonopant G (Indian Journal of Forensic Medicine & Toxicology, 2020)
Covid-19 outbreak is spread all over the world. It is important that all nurses including healthcareprofessional be prepared to care for people affected by such emerging Infectious Diseases (EID. Researchapproach adopted was exploratory survey method. Research hypothesis (Ho) is healthcare preparednessabout Emerging Infectious Diseases (EID is independent of cadre of nurses. Convenient sampling methodwas used. The study was conducted during May 2020 across (Maharashtra). The total 180 nurses of variouscadres were participated in online survey. Semi structured questionnaire was prepared with 30 questions onpreparedness of nurses. However, overall preparedness level was found satisfactory, still there was gap inpreparedness. Preparedness level of Emerging Infectious Diseases (EID is independent of cadre of nurses.(Ho) To test this we applied standard F test for collective comparison of means using ANOVA table. Sincethe computed F ratio is less than the table value the mean, preparedness level of four cadres does not differsignificantly accepting null hypothesis (Ho).